Trends in cannabis use in New Jersey: Effects of COVID‐19 and cannabis legalization - John P. Kane; Andrew Ames; Raj V. Patel; Kaitlyn Voity; Roland Narine; Rimma Perotte; Simon Gelman; Diana McCarthy; Sondra Maureen Nemetski (Journal of the American College of Emergency Physicians Open, 2024)
Abstract Objectives With the legalization of cannabis in New Jersey on April 21, 2022, including the licensing of cannabis dispensaries, concerns have arisen about potential adverse events related to cannabis use. Here, we explore temporal trends and risk factors for cannabis‐related harm in both adult and pediatric cannabis‐related visits at a tertiary care academic institution. Methods We performed a retrospective chart review and temporal trend analysis via the electronic health record from May 1, 2019 to October 31, 2022, covering 2 years before, and 6 months after, cannabis legalization in New Jersey. The pediatric charts identified were analyzed for root causes of adverse events, and changes in the frequency of specific unsafe practices since cannabis legalization were tracked. Results We found that adult cannabis ED‐related visits significantly increased during the COVID‐19 pandemic and remained higher than pre‐pandemic levels for the remainder of the study periods, without a significant change upon legalization. Pediatric rates of cannabis‐related ED visits did not vary significantly during the study period. The vast majority of visits for children aged 0–12 years were related to accidental cannabis exposures—often a household member's edibles—whereas most visits for older children stemmed from intentional cannabis use. Conclusion This project highlights the unintended consequences of wider cannabis access in New Jersey. Notably, cannabis use increased even before its legalization, presumably in response to the COVID‐19 pandemic and its attendant mental health effects. Rates of cannabis use disorder and its highlight of other concurrent psychiatric disorders are important topics for both clinicians and lawmakers to consider.